Networking Institutionalism oleh Kaukus Perempuan Parlemen Lampung dalam Mengoptimalkan Kebijakan Gender - Khairunnisa Maulida; Robi Cahyadi Kurniawan; Hertanto Hertanto (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2021)
The representation of women in parliament is still far from the quota that has been determined in the policy, which is 30% so that the role of women in parliament is still not optimal in fighting for pro-gender equality. The method in this study uses a qualitative method with a descriptive approach, with a number of informants as many as 11 informants with details 2 from the Lampung Parliamentary Women's Caucus management, 6 from government officials in Lampung Province and 1 from public policy observers. The results obtained are that the Parliamentary Women's Caucus in Lampung synergizes with various government agencies in Lampung Province, namely the Office of Women's Empowerment and Child Protection, the General Elections Commission (KPU), collaboration is also carried out with the Damar Non-Governmental Organization, Mass Media and other community organizations that are pro- With gender equality, the goal is to manage the budget and implement work programs, namely optimizing policies that favor gender equality, but from the results of the research the Lampung Women's Parliamentary Caucus has not been able to carry out its role optimally, this is due to a lack of coordination and meetings between the Lampung Parliamentary Women's Caucus officials so that the policy that are in favor of gender also cannot be carried out optimally. 5 aspects of the theory of networking institutionalism, it is known that the organizational aspect is not optimal because there are still internal constraints, namely the lack of intensive coordination between the Lampung Parliamentary Women's Caucus administrators.